CATCH RATE AND CATCH COMPOSITION OF MINI PURSE SEINE IN BUALEMO, BANGGAI DISTRICT - Regi Fiji Anggawangsa; Suwarso Suwarso; Wudianto Wudianto (Indonesian Fisheries Research Journal, 2014)
Small pelagic fishery is the largest potential commodity in the waters of Tomini Bay which reached 64% of the total fish resources. Mini purse seine (soma pajeko) is the major fishing gear that used to utilize small pelagic resources in Tomini Bay. One of the main fishing grounds of mini purse seine vessels in Tomini Bay is in Bualemo and the surrounding waters. The aim of this research was to describe mini purse seine fishery in Bualemo especially about the aspects of the catch rate and catch composition. From the analysis of the daily catch data, there was a fluctuation of the average of catch rate each month. The catch of mini purse seine in Bualemo was dominated by two main species that is malalugis/mackerel scad (Decapterus macarellus) and bigeye scad (Selar crumenophthalmus). The large amount of the young fish (juvenile) caught by mini purse seine caused by the vessels operated around FADs and the mesh size that was less selective.